Nanohybrid thin-film composite carbon molecular sieve membranes. (March 2020) - Ogieglo, W.; Puspasari, T.; Hota, M.K.; Wehbe, N.; Alshareef, H.N.; Pinnau, I.
Abstract: Industrial separations belong to some of the most energy-intensive technological processes because of the reliance on heat-consuming unit operations involving a phase change, such as distillation. Membrane technology promises large cuts to those energy needs; however, its progression is hindered as currently available membranes lack separation performance as well as chemical and mechanical stability. To address these challenges, carbon molecular sieves (CMSs) have long been suggested as promising candidates providing excellent and robust molecular separation performance. In this work, we introduce nanohybrid CMS membranes fabricated by pyrolyzing a polyimide of intrinsic microporosity (PIM-PI) precursor modified by vapor phase infiltration (VPI). In the VPI process, a metal-organic precursor, trimethylaluminum (TMA), first diffuses into the high free volume matrix of the PIM-PI to form a complex with its functional groups. Afterward, water vapor selectively and locally oxidizes the TMA to form nanodispersed Al2 O3 within the PIM-PI matrix. Subsequent inert-atmosphere pyrolysis leads to the formation of Al2 O3 -doped, high-quality, thin-film composite CMS membranes with excellent molecular separation properties for a number of technologically important gas pairs, e.g. CO2 /CH4  > 100, O2 /N2  > 9. The introduction of VPI-doped hybrid CMS membranes allows obtaining extraordinary gas separation performance typical to high temperature undoped CMS at much lower pyrolysis temperatures. This presents significant advantages such as reduction of mechanical failure risk, wider spectrum of possible supports, and reduced fabrication complexity. Graphical abstract: Image 1 Highlights: Introduction of nanohybrid thin-film composite carbon molecular sieve (CMS) membranes Combination of vapor phase infiltration (VPI) and pyrolysis leads to metal oxide–doped CMS Nanohybrid CMS membranes show excellent molecular sieving properties VPI allows reductions of pyrolysis temperatures by 200–300°C The presented concept enables extremely wide fine-tuning possibilities